2023
DOI: 10.1007/s11869-023-01357-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns and trends of the air pollution integrating MERRA-2 and in situ air quality data over Egypt (2013–2021)

Abstract: For best-informed decision-making to improve climate change adaptation and reduce present and future air pollution health hazards, it is essential to identify major trends in spatiotemporal air quality patterns of common air contaminants. This study examined the patterns and trends of SO2, NO2, CO, O3, and particulate matter (PM) air pollutants over 91 monitoring stations in Egypt during 93 months in the August (2013)–April (2021) period. In situ data with their monthly, seasonal, and yearly spatial trends are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…In a study on the extreme temperature events over Egypt, Saleh et al [14] investigated the HW cases during the period from 1980 to 2015 in three governorates in Egypt, with a focus on the major agricultural climatic regions, namely Behira governorate, representing North Delta; Giza governorate, representing Middle Egypt; and Qena governorate, representing Upper Egypt. This study found that Egypt was exposed to several HW events during the last decades, the most pronounced being the HWs of the winter season of 2010 and the summer season of 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on the extreme temperature events over Egypt, Saleh et al [14] investigated the HW cases during the period from 1980 to 2015 in three governorates in Egypt, with a focus on the major agricultural climatic regions, namely Behira governorate, representing North Delta; Giza governorate, representing Middle Egypt; and Qena governorate, representing Upper Egypt. This study found that Egypt was exposed to several HW events during the last decades, the most pronounced being the HWs of the winter season of 2010 and the summer season of 2015.…”
Section: Introductionmentioning
confidence: 99%